2019
DOI: 10.3390/ijerph16050717
|View full text |Cite
|
Sign up to set email alerts
|

Stomach Cancer and Exposure to Talc Powder without Asbestos via Chinese Herbal Medicine: A Population-Based Cohort Study

Abstract: The present investigation was designed to explore the risk of stomach cancer by oral intake of talc powder without asbestos. We conducted a population-based cohort study on a randomly sampled cohort from Taiwan’s health insurance database, with population of 1,000,000. The study participants were followed up through 2013. The outcome event of interest was the diagnosis of stomach cancer. The exposure of interest was the prescription of talc powder. Cox regression analyses were performed respectively. There wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Most of the studies on the health benefits of the supplementation of micronutrients, especially in vitro studies, used highly concentrated or purified preparations of the micronutrients delivered directly or through a safe vehicle. Dietary supplements include several additives for different purposes, which can be associated with adverse effects on their own [ 57 ], specifically in the light of a lack of regulation by the Food and Drug Administration (FDA). Other considerations regarding these studies are the dosage and study population.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on the health benefits of the supplementation of micronutrients, especially in vitro studies, used highly concentrated or purified preparations of the micronutrients delivered directly or through a safe vehicle. Dietary supplements include several additives for different purposes, which can be associated with adverse effects on their own [ 57 ], specifically in the light of a lack of regulation by the Food and Drug Administration (FDA). Other considerations regarding these studies are the dosage and study population.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the case of talc powder, very careful attention is required when applying it because it can cause cancers (30,31). Viscum album L. extract has been used as an auxiliary herbal medication for cancer treatment for more than 80 years in Europe (32), particularly against malignant pleural effusion, after successful chemical pleurodesis with bleomycin (2,10).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have explored the link between talc and cancer with a recent publication concluding that exposure to talc was associated with an increased risk of gastric cancer (1.21 (95% CI: 1.03-1.42, P ¼ 0.02) [25]. Earlier, a population-based cohort study in Taiwan with a population of 1,000,000 showed a HR of 2.13, 95% CI 1.54-2.94, P < 0.001 [26].…”
Section: Occupational Exposures and Gastric Cancer Riskmentioning
confidence: 99%